Analysis of the Determinants of Earnings Smoothing: The Case of Tunisian Companies (Global Journal of Management and Business Research, 2013)
The objective of this paper is to analyze the impact of the determinants of income smoothing in Tunis, which is to reduce the volatility of results. From a sample of 50 companies listed on the stock exchange of Tunis (Tunis Stock Exchange) during the period 2006-2010. We have developed an explanatory model of earnings management practices based on logistic regression. Our results show that the use of debt companies, calling the companies audited by a firm of "big six" provides a smoothing of results high. In the end, this original work of Tunisian data led to very carefully reinterpret the results of previous studies.
Keywords: earnings management; manager; operating profit